Творчество Виктора Астафьева в польской литературной критике - Popiel-Machnicki, Wawrzyniec; Osiewicz, Bartosz (Studia Rossica Posnaniensia, 2015)
This article is devoted to the reception of Viktor Astafyev’s works by Polish literary critics. The authors examined Polish critical studies starting from the 1990s. Those elements that have not been analyzed yet are used to shed light on the works of this village prose writer. At the same time, the authors underline Viktor Astafyev’s religious awareness, pro-ecological way of thinking and his involvement in Russia’s current problems.